PENERAPAN METODE AMTSILATI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI MADRASAH DINIYAH - Ahmad Faroq; Abdurrahim Said (LP3M IAI Al-Qolam, 2021)
The motivation of students in Madrasah Diniyah Iqoomatul Islam decreased because ineffective method applied in the learning process. At the end of 2017 at Madrasah Diniyah Iqoomatul Islam apply a method of learning namely Amtsilati to improve the spirit of Its students. This study aims to answer the questions: how the implementation of Amtsilati method and how the role of Amtsilati Method in improving student motivation in this Madrasah Diniyah. This research uses descriptive qualitative method. Data obtained through interviews and observations. The subjects of the study are the principal, the teachers, and the students of Amtsilati. Data analysis uses data reduction, data presentation, and conclusions. Data validities check for confidence test using Extension of Participation, Persistence of Observation, Triangulation, Peer Checking, and Member Checks. The result of this study shows that the Amtsilati Method has a significant role to understand Arabic texts, provides positive values, consistent learning, as well as conducive learning atmosphere in improving student learning motivation.